Pilgrimage as Self-Discovery in an Ecological Community - Kip Redick (Religions, 2023)
Pilgrims become open to self-discovery in a Gestalt of the personal and communal. Traditional pilgrimage integrates pilgrims into a community of faith. Long-distance hikes through wilderness, such as the Appalachian Trail, may be interpreted from this lens. However, the environment/space/place of wilderness situates pilgrims beyond a traditional religious frame. The sacred does not manifest from a schema of established religious symbols because wilderness trails disrupt preconceptions, breaking through the self’s strategies of centering. The disruption of one’s prior orientation to community, customs, and conventions that form the self’s symbolic schema opens the hiker to what Levinas references as “the delirium that comes from God [as] a divine release of the soul from the yoke of custom and convention”. The other as transcendent presents herself and exceeds “the idea of the other in me,” (Levinas). Pilgrims may discover an existential dialogue with the sacred other, the human or extra-human. The Gestalt of the personal and communal extends beyond traditional boundaries, encompassing human and extra-human beings.